CORRELATION BETWEEN PREGNANT PHYSICAL ACTIVITY WITH PREECLAMPSIA IN WORKING AREA OF TEMPUREJO PUBLIC HEALTH CENTER, JEMBER - Desi Trisari; Dini Kurniawati; Peni Perdani (Journal of Nursing Science Update (JNSU), 2019)
Preeclampsia is one of pregnancy complication which is the biggest cause of maternal and infant mortality. The cause is not yet known but many risk factors can affect the occurrence of preeclampsia, one of which is physical activity. The purpose of this study was to analyze the correlation between the physical activity of pregnant women with the incidence of preeclampsia in the work area Tempurejo Public Health Center, Jember. The research design used in this study was analytical-survey with a cross-sectional approach. Respondents in this study were 77 pregnant women taken by total sampling. Data collection was conducted using PPAQ (Pregnancy Physical Activity Questionnaire) and maternal and child health book. Data analysis was performed using the chi-square test. This study found that 39 respondents (50,6%) showed good physical activity. The chi-square test showed no correlation between the physical activity of pregnant women and the incidence of preeclampsia in the work area of Tempurejo Community Health Center, Jember with the p-value 0.557 (P > Î± = 0,05). There is no difference in physical activity between preeclampsia and non-preeclampsia women because all respondents are included in the mild preeclampsia group. In mild preeclampsia, subjective symptoms are not felt by pregnant women so that some pregnant women do not limit physical activity and pregnant women who work still do work activities such as normal pregnant women. Health workers are expected to provide nursing care related to the prevention of preeclampsia way through education and routine antenatal care.